A network traffic flow model for motorway and urban highways - Yang, Chao; Remenyte-Prescott, Rasa; Andrews, John (Palgrave Macmillan, 2014)
The research reported in this paper develops a network level traffic flow model (NTFM) which is applicable for both motorway and urban roads. It forecasts the traffic flow rates, queue propagation at the junctions and travel delays through the network. NTFM uses sub-models associated with all road and junction types which comprise the highway. The flow at any one part of the network is obviously very dependent upon the flows at all other parts of the network. To predict the two-way traffic flow in NTFM, an iterative simulation method is executed to generate the evolution of dependent traffic flows and queues. To demonstrate the capability of the model it is applied to a small case study network and a local Loughborough-Nottingham highway network. The results indicate that NTFM is capable of identifying the relationship between traffic flows and capturing traffic phenomena such as queue dynamics. By introducing a reduced flow rate on links of the network then the effects of strategies employed to carry out roadworks can be mimicked.